Contribution of Nitrogen to Growth of Maize in Legume-maize Rotation on Limed Ultisols - Abd Rahim, Anuar; Shamsuddin, Zulkifli; Yaacob, Othman (Universiti Putra Malaysia Press, 1994)
Liming of soils and the use of legume residues in a crop rotation are considered good approaches to reduce the constraints of high aluminium and low native nitrogen affecting annual food crop production in Ultisols. Using this approach the values of nitrogen contributed to maize in three groundnut (L)-maize (M) sequences (LMLM, MLLM and LLLM) in an intensive rotational cropping system were estimated. The estimates were made by subtracting the total N-uptake by maize in the zero N-fertilized monocropping from the total N-uptake by maize under the respective legume-maize rotation. The results showed that it is possible to sustain an increased yield of groundnut and maize on limed Ultisols. In the groundnut-maize cropping system, the average N contribution was after one, two and three successive groundnut crops was 19, 33, and 56 kg N ha-1. The latter estimate is about one-third of the newly recommended total N requirement of maize, 159 kg N ha-1.